Pokora jako ctnost pro úspěch i selhání - Pacovská, Kamila (Filosofický ústav Akademie věd České republiky, 2025)
The prevailing conception of humility in contemporary anglophone discussions equates humility with a modesty that has application in situations of success: modes ty is a virtue that regulates a person’s reaction to her own great achievement. A hum ble or modest person does not show off, does not ridicule her less fortunate col leagues, etc. I will contest this conception, claiming that humility has at least an equally important role in dealing with failure or unsuccess. Analysing two scenarios of inappropriate response to failure, I will show that humility fights two tendencies: on the one hand, it corrects the tendency to obstinately deny one’s flaws and errors while, on the other hand, it corrects the tendency to get cast down and discouraged by them. The third and final scenario, in which the failing person undergoes a hum bling experience, leads to a new, symmetrical conception of humility based on the person’s conception of her Self and its value. Such transformative experience does not amount to abating one’s sense of one’s value, but to freeing it from the influence of the “status games.”
Humility as a Virtue for Success and Failure
Keywords: pride; humility; modesty; humbling experience; success; achievement; failure; unsuccess; education; praise and blame; shame; status games